DATA ANALYSIS TO SUPPORT AUTOMATIC DRIVER WARNINGS FOR A CYBER-PHYSICAL ACCIDENT PREVENTION SYSTEM - BILINSKA, ADA; BINKOVSKYI, YAROSLAV; HOLOVATIUK, ANDRII; MELNYCHUK, DENIS; HOVORUSHCHENKO, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In today’s world, road safety remains one of the most pressing issues, as car accidents result in thousands of injuries and deaths every year. One of the key aspects of preventing accidents is a system that warns drivers of possible hazards on the road. It is important to consider the role of warning messages for drivers and their impact on the overall level of road safety. This article discusses the importance of driver warnings as one of the essential elements of road safety. Failure to warn the driver in a timely manner about possible vehicle problems and other dangerous situations can lead to serious consequences, including accidents and injuries. Road safety problems can arise for various reasons, including violations of traffic rules, technical malfunctions of cars, changes in weather conditions and other factors. For example, drivers who do not follow the speed limit, make improper overtaking or use mobile phones while driving increase the risk of accidents and injuries. On the other hand, malfunctions in automotive technology, such as problems with brakes, steering or lighting, can lead to unexpected situations and accidents. The lack of warning notifications for drivers when there are problems with the car can lead to serious consequences. Due to proper informing of drivers about potential dangerous situations on the road, they have the opportunity to react in time and avoid possible accidents. Many different reasons were considered that could lead to dangerous situations on the road, such as breaking or not following traffic rules, changes in weather conditions, and technical problems with the vehicle. As a result of the research, it can be understood that quick analysis of input data from vehicle subsystems and display of this data on the screen to the user will help to avoid undesirable situations and increase safety while using the vehicle. The purpose of this article is to reveal the main aspects of data analytics to support automatic driver warnings and provide insight into how cyber-physical systems can improve road safety and reduce the risk of accidents.